Impact of Neurological Follow-Up on Early Hospital Readmission Rates for Acute Ischemic Stroke. (July 2017) - Allen, Alexander; Barron, Todd; Mo, Ashley; Tangel, Richard; Linde, Ruth; Grim, Rodney; Mingle, John; Deibert, Ellen
Introduction: Despite advances in stroke care, readmission rates for patients with ischemic stroke remain high. Although factors such as age, diabetes, and continuous use of antiplatelet agents have been found to predict readmission rates, the impact of after-hospital care has not been examined. Methods: The present study reviewed the charts of 416 patients with acute ischemic stroke and recorded stroke-related comorbidities, neurology follow-up within 21 days, readmission at 0 to 30 days, readmission at 31 to 90 days, and any reasons for readmission. Results: For those readmitted within 0 to 30 days, reasons for readmission were other medical conditions (62.5%), recurrent stroke (30.4%), and elective procedure (7.1%). For those readmitted within 31 to 90 days, reasons for readmission were other medical conditions (62.3%), recurrent stroke (15.1%), and elective procedure (22.6%). There was no significant relationship between being evaluated within 21 days and readmission at 0 to 30 or 31 to 90 days. However, those who did have a neurology follow-up at any point in time had a lower readmission rate of 10.6% compared to those who never came back (19.2%, P = .017). Patients with coronary artery disease and diabetes had a significantly higher likelihood of readmission within 0 to 30 days. Conclusion: The present study suggests that neurology follow-up at any point in time for patients with acute ischemic stroke may reduce short-term readmissions, but special attention to optimizing management of other underlying medical conditions, coronary artery disease, or diabetes may also help reduce overall readmissions. Patients with stroke, therefore, may benefit from a follow-up with both the primary care and neurology in a coordinated fashion to prevent early readmissions at 30 days.